2012
DOI: 10.1016/j.toxicon.2012.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a cone snail's killer cocktail – The milked venom of Conus geographus

Abstract: “Snails can kill” is a statement that receives much disbelief. Yet the venom from Conus geographus, as delivered by a disposable hypodermic-like needle, has indeed killed many unsuspecting human victims. Our understanding of their milked venom the essence of these fatalities, is in itself non-existent. Here, we present the molecular mass analysis of the milked venom of C. geographus, providing the first insight into the composition of its deadly cocktail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…1). All chromatograms display complex compositions and excellent resolution that compares to previously reported RP-HPLC profiles of injected venom from C. purpurascens [21,27] and other fish-hunting Conus species (C. geographus [28], C. consors [12], C. striatus [16], and C. ermineus [20]). There were between 97 and 150 fractions manually collected from the injected venom sample of each specimen.…”
Section: Rp-hplc Chromatographic Profiles Of Injected Venom and Maldisupporting
confidence: 51%
“…1). All chromatograms display complex compositions and excellent resolution that compares to previously reported RP-HPLC profiles of injected venom from C. purpurascens [21,27] and other fish-hunting Conus species (C. geographus [28], C. consors [12], C. striatus [16], and C. ermineus [20]). There were between 97 and 150 fractions manually collected from the injected venom sample of each specimen.…”
Section: Rp-hplc Chromatographic Profiles Of Injected Venom and Maldisupporting
confidence: 51%
“…An alternative explanation for the observations on the behavioral cadre of Conus geographus that inject venom before completely engulfing their prey is that motor cabal components are used both for prey capture, as well as for defense. This is supported by findings of Dutertre et al (2014) on the presence of motor cabal toxins (μ-GIIIA and ω-GVIA) in the defense-evoked venom and a study by Bingham et al (2012) that showed that these compounds were also present in the predatory venom of C. geographus .. The ecological conditions of the Australian Conus geographus cadre presumably make direct injection of lightning-strike cabal components more effective than release into the water (but would therefore result in the snail only being able to capture one fish prey per foraging event).…”
supporting
confidence: 58%
“…See https://www.youtube.com/watch?v=FYh2zeAsRXY). However, a diversity of foraging behavior has been reported for Conus geographus from some Australian localities; as documented by Bingham and co-workers for Australian specimens (Bingham et al 2012). Even in this survey of Australian specimens, most C. geographus engulf their prey before envenomation, but a minority (5/27) were observed to extend their proboscis in the presence of prey.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Despite Arg13 replacing the conserved Tyr13 critical for potent Ca v 2.2 inhibition in piscivorous ω-conotoxins 22 , 23 , the pharmacology of MoVIA and MoVIB closely resembles that of ω-conotoxins from fish-hunting cone snails, including those from C. consors , C. catus , C. fulmen , C. geographus , C. magus , C. radiatus , C. striatus and C. tulipa 22 , 23 , 38 , 43 , 44 . Indeed, MoVIA and/or MoVIB may be ancestral to GVIIA and/or GVIIB, given Tyr13 is also replaced by Arg13 and both have similar elongated and non-amidated C-termini, albeit those from C. geographus are ~100-fold lower affinity than the highly homologous GVIA at mammalian Ca v 2.2 16 , 45 . Similarly, the MVIIA-[Y13R] analogue also showed ~100-fold decrease in binding affinity over MVIIA and no functional activity at mammalian Ca v 2.2.…”
Section: Discussionmentioning
confidence: 99%